2022
DOI: 10.3389/fnins.2022.916055
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte development in the cerebral cortex: Complexity of their origin, genesis, and maturation

Abstract: In the mammalian brain, astrocytes form a heterogeneous population at the morphological, molecular, functional, intra-, and inter-region levels. In the past, a few types of astrocytes have been first described based on their morphology and, thereafter, according to limited key molecular markers. With the advent of bulk and single-cell transcriptomics, the diversity of astrocytes is now progressively deciphered and its extent better appreciated. However, the origin of this diversity remains unresolved, even tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 102 publications
0
20
0
2
Order By: Relevance
“…When we characterized Ptprd expression in this novel mouse model, we observed that transcripts were reduced by more than half at E16.5 ( Figure 1B ) when gliogenesis started. At this embryonic stage, some cells derived from dorsal structures are expected to have migrated to the forebrain ( Gorski et al, 2002 ; Clavreul et al, 2019 ; Shen et al, 2021 ; Clavreul et al, 2022 ), which explains why Ptprd expression is not fully abolished in the PTPRD cKO mouse cortex. Moreover, we cultured E16.5 cortical NPCs as neurospheres and measured Ptprd expression after 7 DIV ( Figure 1C ), finding that forebrain NPCs derived from PTPRD cKO embryos lacks Ptprd expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When we characterized Ptprd expression in this novel mouse model, we observed that transcripts were reduced by more than half at E16.5 ( Figure 1B ) when gliogenesis started. At this embryonic stage, some cells derived from dorsal structures are expected to have migrated to the forebrain ( Gorski et al, 2002 ; Clavreul et al, 2019 ; Shen et al, 2021 ; Clavreul et al, 2022 ), which explains why Ptprd expression is not fully abolished in the PTPRD cKO mouse cortex. Moreover, we cultured E16.5 cortical NPCs as neurospheres and measured Ptprd expression after 7 DIV ( Figure 1C ), finding that forebrain NPCs derived from PTPRD cKO embryos lacks Ptprd expression.…”
Section: Resultsmentioning
confidence: 99%
“…Additional results showed decreased astrocytes and oligodendrocytes in the PTPRD cKO postnatal cortex, which correlates with reduced myelin expression in the corpus callosum. Since most perinatal cortical astrocytes and their precursors originate from cortical NPCs and astrocyte local proliferation ( Tsai et al, 2012 ; Clavreul et al, 2019 ; Vogel and Wegner, 2021 ; Clavreul et al, 2022 ), the reduced number of radial glia cells (Pax6+) and astrocytic progenitors (Sox9+) ( Kang et al, 2012 ; Martini et al, 2013 ; Sloan and Barres, 2014 ), and the postnatal reduction of GFAP+ astrocytes observed in PTPRD cKO mouse cortex indicates that PTPRD has a role in astrogliogenesis. This observation can also be extended to oligodendrogenesis since most OPCs and oligodendrocytes originated from EMX1+ NPCs are in the main areas studied here, such as deep cortical layers and white matter ( Shen et al, 2021 ), suggesting that PTPRD would also regulate oligodendrogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ablation of TSP1/2 in adult astrocytes did not alter performance during operant tasks. However, when we ablated TSP1/2 in neonatal astrocytes, targeting a period corresponding to the start of astrocyte morphogenesis, synapse development, and normal expression of TSP1/2 in the cortex [106,107], we found a significant decrease in performance during high-effort tasks. This is consistent with previous findings in the literature showing that cortical astrocytes express TSP1/2 within the first two weeks of post-natal development, but the expression is diminished by P21 [29].…”
Section: Discussionmentioning
confidence: 99%
“…The neurons thus generated delaminate from the VZ and migrate, through the intermediate zone (IZ), to the cortical plate (CP) ( Cardenas et al, 2018 ; Cardenas and Borrell, 2020 ). The newborn BPs also delaminate from the VZ but migrate only to the SVZ, where, depending on the mammalian species, they undergo a varying degree of self-amplification, followed by the generation of neurons and later of macroglial cells (astrocytes and oligodendrocytes; a process called gliogenesis) ( Kriegstein and Alvarez-Buylla, 2009 ; Taverna et al, 2014 ; Tabata, 2015 ; Ohtsuka and Kageyama, 2019 ; Clavreul et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%